2017
DOI: 10.1016/j.celrep.2017.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mechanisms for SHP2 Binding and Activation Are Exploited by Geographically Distinct Helicobacter pylori CagA Oncoproteins

Abstract: Helicobacter pylori East Asian CagA is more closely associated with gastric cancer than Western CagA. Here we show that, upon tyrosine phosphorylation, the East Asian CagA-specific EPIYA-D segment binds to the N-SH2 domain of pro-oncogenic SHP2 phosphatase two orders of magnitude greater than Western CagA-specific EPIYA-C. This high-affinity binding is achieved via cryptic interaction between Phe at the +5 position from phosphotyrosine in EPIYA-D and a hollow on the N-SH2 phosphopeptide-binding floor. Also, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 30 publications
3
104
0
Order By: Relevance
“…A quantitative biochemical study revealed that the East Asian CagA (ABD)specific EPIpYA-D peptide binds to the N-SH2 domain of SHP2 100-fold more strongly than the Western CagA (ABC)-specific EPIpYA-C peptide. The phenylalanine (F) residue at the pY + 5 position of the EPIpYA-D peptide was found to form a high-affinity monovalent bond with the hollow pocket on the N-SH2 phosphopeptide-binding floor of SHP2 136 (Fig. 3).…”
Section: Sequence Polymorphisms Of Caga That Confer Differential Oncomentioning
confidence: 99%
“…A quantitative biochemical study revealed that the East Asian CagA (ABD)specific EPIpYA-D peptide binds to the N-SH2 domain of SHP2 100-fold more strongly than the Western CagA (ABC)-specific EPIpYA-C peptide. The phenylalanine (F) residue at the pY + 5 position of the EPIpYA-D peptide was found to form a high-affinity monovalent bond with the hollow pocket on the N-SH2 phosphopeptide-binding floor of SHP2 136 (Fig. 3).…”
Section: Sequence Polymorphisms Of Caga That Confer Differential Oncomentioning
confidence: 99%
“…Mutations of PTPN11 (the gene coding for SHP2) cause more than 30% of cases of juvenile myelomonocytic leukemia (JMML) [Tartaglia 2003;2004 a] and are variably found in other childhood malignancies [Tartaglia 2003[Tartaglia , 2004bGrossmann 2010]. In addition, SHP2 is required for survival of receptor tyrosine kinases (RTK)-driven cancer cells [Chen 2016], plays an important role in resistance to targeted cancer drugs [Ahmed 2019], is a mediator of immune checkpoint pathways [Okazaki 2013] and is involved in the induction of gastric carcinoma by H. pylori [Hayashi 2017]. PTPN11 mutations also cause Noonan syndrome and Noonan syndrome with multiple lentigines, two disorders belonging to a family of rare diseases collectively known as RASopathies [Tartaglia 2001;Tartaglia 2004a;Tartaglia 2010].…”
Section: The Sh2 Domain-containing Protein Tyrosine Phosphatasementioning
confidence: 99%
“…Hydrophobic, anionic and cationic residues are colored in green, red and blue, respectively. pY numbers refer to the human sequence, except for H. pylori CagA, where the sequence refers to the EPIYA-D segment [Hayashi 2017]. Relative dissociation constant (Kd) values, are normalized to that of IRS-1 pY1172 [Sugimoto 1994], i.e.…”
Section: Phosphopeptide Sequence Selectivity Of the N-sh2 Domain Of Shp2mentioning
confidence: 99%
“…5,9,10,11,12 Recent studies suggested SHP2 inhibition as a promising strategy for treating a large class of receptor tyrosine kinase-driven cancers 13 and for combating resistance to targeted anticancer therapies. 14,15,16 In addition, SHP2 plays a role in Helicobacter pylori-induced gastric cancer mediated by activation by the bacterial protein CagA, 17 and SHP2 is responsible for the suppression of T-cell activation by programmed cell death-1 (PD-1), a receptor hijacked by tumor cells for evading the immune response. 18 All these recent discoveries indicate SHP2 as an attractive target in future anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…According to this hypothesis, phosphopeptide binding to the SH2 domains simply stabilizes the fraction of active SHP2, only after dissociation of N-SH2 from the PTP domain has already taken place. 7,17,28 Second, according to an "induced fit" model, peptide binding might take place in the inactive state of SHP2, triggering the concomitant opening of the protein. 29 However, since the N-SH2 binding site is closed in the inactive state, phosphopeptide binding to the inactive state would require a conformational transition of the N-SH2 domain with respect to the crystal structure.…”
Section: Introductionmentioning
confidence: 99%